Detecting semi-referees in the Plackett-Luce model - Omid Naghshineh Arjmand; Nastaran Mirzaei (AUT Journal of Mathematics and Computing, 2023)
In this paper, we use the Plackett-Luce model for detecting some referees who judge arbitrariness with inaccuracy or without paying enough attention, which is called Semi-referees. We will investigate our method by simulation and sample of real data.